UJI TINGKAT KEMATANGAN BUAH MANGGA MENGGUNAKAN PIGMEN ANTOSIANIN DARI BUNGA TELANG (Clitoria ternatea) - Dhanang Puspita; Monang Sihombing; Karina Permata (UNIVERSITAS PGRI MADIUN, 2021)
Increased consumption of fruit requires consumers to understand how to choose good and ripe fruit. The level of fruit maturity can be known based on physical characteristics, including the parameters of size, weight, skin color, fragrance of the fruit, and the level of hardness of the fruit flesh. Determining the level of fruit maturity based on physical characteristics has a weakness that is subjective and inconsistent. Making indicators based on natural dyes, namely anthocyanins, to determine the level of sweetness of the fruit. The purpose of this research is to use anthocyanin pigments as an indicator of fruit sweetness level to determine fruit maturity. This research is an experimental laboratory and qualitative descriptive analysis with stages; Sample Extraction, Indicator Making, Indicator Application, Fruit Acidity Testing, Data Analysis. Based on the results of the study, there were quite visible color differences on toothpicks after being inserted into the fruit samples with a sweet taste and the fruit samples with a sour taste. The indicator shows that fruit with a sour taste (pH < 3) changes color from blue to reddish purple. If the taste is not too sour (pH 5), it does not experience a significant color change. In conclusion, the anthocyanins in telang flower can be used as an indicator solution because they have a blue color at neutral pH, a reddish color at pH = 2, the red color fades at pH = 3 and 4, and there is no color change at pH 5.